Perception of Undergraduate Students on the Utilization of Social Media to Enhance Learning in University of Ilorin - Gboyega Ayodeji Aladesusi; Ahmed Idris Issa; Sunday Oluwasegun Abodunrin; Oluwarotimi Ayodele Boris; Ebenezer Omolafe Babalola; Kehinde Muritala Nuhu (Universitas Pendidikan Indonesia (UPI), 2021)
The objective of this study was to (i) investigate the available social media used by undergraduates for Learning, (ii) examine frequency of utilization of social media to facilitate learning, and (iii) examine undergraduates’ perception of the use of social media to facilitate learning. The study employed descriptive research of the survey type to elicit responses from 258 undergraduates. The research questions were answered considering independent t-test statistics. The results indicated that (i) majority of the social media available and adequate within the university, (ii) social media frequently used to enhance learning, (iii) a positive perception towards the use of social media in instruction, and (iv) no significant difference between male and female students in the frequency of use of social media and students’ perception on the use of social media for learning. Undergraduate students should adopt the use of social media for learning since this technology is useful for learning. Seminars, workshops, and conferences should be organized for male and female undergraduates on the usefulness of social media for learning since it is no gender bias.